DISTRIBUSI DAN KEANEKARAGAMAN KUPU-KUPU (LEPIDOPTERA) DI GUNUNG MANADO TUA, KAWASAN TAMAN NASIONAL LAUT BUNAKEN, SULAWESI UTARA - Roni Koneri; Saroyo Saroyo (Bumi Lestari Journal of Environment, 2012)
Butterfly (Lepidoptera) are beneficial as pollinators, silk producers, indicators of environmentalquality, and are appreciated for their aesthetic value. The objective of the research was tostudy analyze the distribution and diversity of butterfly (Lepidoptera) in Manado Tua Montauin,region of Bunaken National Marine Park, North Sulawesi. This research was conducted overtwo months, between Juni and Juli, 2011 using a sweeping technique applied to follow the linetransect length of 1000 meters at random in each habitat type (primary forest, secondary forest,gardens and shrubs). The result found 28 species from 4 families (Papilionidae, Nymphalidae,Lycaenidae, and Pieridae ). The distribution of each butterfly species is different along habitat.The highest diversity index value (H‘=2.16) was found at shrubs, while the lowest diversityindex value (H‘=0.33) was found at primary forest. This research is expected to be the basicdata on butterfly diversity and effects of habitat changes on the diversity and distribution ofbutterfly in North Sulawesi